The employee's perception on the transformational leadership style of the employer / Mohd Azril Hisyam Mohamad Daud - Mohamad Daud, Mohd Azril Hisyam (2017)
The study that the employee's perception on the transformational leadership style of the employer is depending on the leadership style that the leader use. This study addressed three main purpose, which are: (1) to identify the employee's perception towards the transformational leadership style of the employer, (2) to examine to which extend the transformational leadership style of the employer can be explained by the sub domain and (3) to examine the difference in perceptions towards the transformational leadership style of employers between gender. This study was distributing the questionnaire to the employees at the Ministry of Youth and Sport at Paroi. There have 23 items of the transformational leadership style (Collin Powell, 2015) was distribute among 140 employees (n = 124) and the age are range 19 - 45 years old. The primary finding in this study is the employees was preferring the leader was using the charisma attitude. The item that using to identify the transformational leadership style of the employer are: (1) Responsiveness, (2) Charisma, (3) Vision, (4) Self-development, (5) Social. There is the item to of the employees' perception in the transformational leadership style. This study also provides an empirical data for future study in this study.